An audit of the prevalence of abnormal fasting blood glucose levels in patients presenting for elective surgery at a selection of Western Cape government hospitals - Biesman-Simons, Tessa (Department of Anaesthesia and Perioperative Medicine, 2020)
Background. Diabetes mellitus (DM) is a common condition. The high burden of undiagnosed DM and lack of large population studies make accurate prevalence estimations difficult, especially in the surgical environment. Furthermore, poorly controlled DM is associated with an increased risk of perioperative complications and mortality. Objectives. The primary objective was to establish the prevalence of DM in elective adult non-cardiac, non-obstetric surgical patients in Western Cape hospitals. The secondary objectives were to assess the glycaemic control and compliance with treatment of known diabetics. Methods. This was a five-day, multicentre, prospective observational study performed at six government-funded hospitals in the Western Cape. Screening for DM was done using fingerprick capillary blood glucose (CBG) testing. Patients found to have a CBG of ≥ 6.5 mmol/L had an HbA1c level done. DM was diagnosed based on the Society for Endocrinology, Metabolism and Diabetes of South Africa (SEMDSA) diagnostic criteria. Patients known with DM had an HbA1c performed and Morisky Medication Adherence Scale (MMAS-4) questionnaires completed, to assess glycaemic control and compliance with treatment. Results. Of the 379 participants, 61 were known diabetics (16.15%; 95% CI 12.4-19.8%). After exclusion of eight patients with incomplete results, a new diagnosis of DM was made in five out of 310 patients (1.6%; 95% CI 0.2-3.0%). Overall prevalence of DM was 17.8% (66/371; 95% CI 13.9-21.7%). HbA1c results were available in 57 (93.4%) of the 61 known diabetics. Of these 27 (47.4%; 95% CI 34.4-60.3%) had an HbA1c level≥8.5% and 14 (24.6%; 95% CI 13.4 - 35.8%) had an HbA1c ≤7%. Based on positive responses to two or more questions on their MMAS-4 questionnaires, 12 out of 60 participants (20%) were deemed non-compliant. Conclusion. There is a low rate of undiagnosed DM in our elective surgical population; however there is a large proportion of poorly controlled DM. Since poorly controlled DM is known to increase postoperative complications, this likely increases the burden of perioperative care. Resources should be focused on improvement of long-term glycaemic control in patients presenting for elective surgery.